Orientation-Dependent Solvatochromism in Ferrocenyl Pyrimidinium Conjugates: Comparative Analysis and Theoretical Insights - Aliaga-Vidal, C; Aliaga-Vidal, C; Dominguez-Caru, M; Vidal-Palomo, M; Vidal-Palomo, M; Aburto-Bernal, I (Elsevier Ltd, 2025)
New ferrocenyl-2-pyrimidinium solvatochromic conjugates were synthesized and their solvatochromic inverted behavior was compared to that of ferrocenyl-4-pyrimidinium dyes. These results were rationalized using EPR spectroscopy, multiparametric studies, density functional theory (DFT) calculations, and Monte Carlo simulations. The present work illustrates how a change in the orientation of the donor/acceptor pair in ferrocene-based dyes controls the solvatochromic shift ranges and inversion points, providing a new tool for the future design of ferrocenyl push-pull dyes with controlled polarity-sensing capabilities © 2024 Elsevier Ltd